1990
DOI: 10.1007/bf01625731
|View full text |Cite
|
Sign up to set email alerts
|

Localization of endogenous osteocalcin in neonatal rat bone and its absence in articular cartilage: Effect of warfarin treatment

Abstract: Immunocytochemistry after cryoultramicrotomy was used to localize endogenous osteocalcin in bone (calvaria, femoral diaphysis) and epiphyseal femoral cartilage from 8-day-old rats treated (or mot) for 7 days with warfarin. Ultrathin frozen sections were incubated with goat antiserum against rat osteocalcin at high dilutions (2 x 10(-4) to 2 x 10(-6). In calvaria and femur of untreated rats, endogenous osteocalcin was observed in osteoblasts (cytoplasm and nucleus) and in the collagenous matrix. Osteocalcin app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
41
0

Year Published

1992
1992
1998
1998

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 37 publications
1
41
0
Order By: Relevance
“…Both hypertrophic chondrocytes and osteoblasts have the ability to induce mineralization of the extracellular matrix and to produce alka- line phosphatase (ALP) ~ (1), osteopontin (OP) (11,29,45), osteonectin (21), matrix Gla protein (MGP) (2,12,17), and the Ch21 protein (9). Bone Gla protein (BGP, also called osteocalcin), another osteoblast marker (35), is present at low levels in the calcified cartilage matrix surrounding hypertrophic chondrocytes in vivo (4,28,29). Studies with chondrocytes in culture have shown that after the cells became hypertrophic they produced type I collagen and BGP (3,8,24,37,41,42), which led to the suggestion that these cells could acquire osteoblastic properties.…”
mentioning
confidence: 99%
“…Both hypertrophic chondrocytes and osteoblasts have the ability to induce mineralization of the extracellular matrix and to produce alka- line phosphatase (ALP) ~ (1), osteopontin (OP) (11,29,45), osteonectin (21), matrix Gla protein (MGP) (2,12,17), and the Ch21 protein (9). Bone Gla protein (BGP, also called osteocalcin), another osteoblast marker (35), is present at low levels in the calcified cartilage matrix surrounding hypertrophic chondrocytes in vivo (4,28,29). Studies with chondrocytes in culture have shown that after the cells became hypertrophic they produced type I collagen and BGP (3,8,24,37,41,42), which led to the suggestion that these cells could acquire osteoblastic properties.…”
mentioning
confidence: 99%
“…Although the presence of osteocalcin antigenicity in the nucleus appears very difficult to explain, we are inclined to believe that cultured cells obtained in our system were osteoblasts. The presence of ALP and osteocalcin in our cultured bone cells and the absence of any osteocalcin synthesis in fibroblasts, osteoclasts, and chondrocytes (BoIvIN et al, 1990) provided rationales for justification of this osteoblast phenotypic expression.…”
Section: Discussionmentioning
confidence: 95%
“…The existence of osteocalcin was demonstrated in the cultured rat osteosarcoma cell clone ROS 17/2, osteoblasts and bone matrix in the mineralization front (NISHIMOTO and PRICE, 1980;PRICE et al, 1981;BIANCO et al, 1985;GROOT et al, 1986;THAVARAJAH et al, 1986;CAMARDA et al, 1987;OHTA et al, 1989;BOIvIN et al, 1990). Osteocalcin was also detected in osteocytes.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations